Expected Impacts of COVID-19: Considering Resource-Limited Countries and Vulnerable Population - Gashaw, Tigist; Hagos, Bisrat; Sisay, Mekonnen (Frontiers in Public Health, 2021)
Coronavirus disease in 2019 emerged in Wuhan, Hubei Province, China, in December 2019. After a month, it was declared a global threat to public health. the effects of the pandemic could be socio-economic, undermining the health system and risking livelihoods. Vulnerability to this infection has been associated with underlying comorbidities such as hypertension, diabetes, coronary heart disease, chronic respiratory diseases, cancer, and compromised immune systems. And co-morbidity has been common to the elderly, the disabled, and the homeless. In addition, more severe coronaviral disease outcomes have been reported in older males than females. Nonetheless, multiple variables are related to the concept of cultural gender that should be taken into account as women in more affected sectors are economically disadvantageous and over-represented. Similarly, although children are not the face of this pandemic, calamity has a profound effect on their welfare, especially for those living in poor and inconvenient situations. Moreover, the economic influence could be profound and universal when viewed through a migration lens as it is exacerbating xenophobic and discriminatory treatment. Protection measures to mitigate the outbreak of a pandemic, such as social distancing, may reduce social support for certain categories relied on for their day-to-day activities. The mental health of people would definitely be affected by the additional psychosocial burden of the pandemic, particularly in vulnerable groups. Integrated approaches are therefore mandatory to assist these groups and contain the pandemic.